Peningkatan Kompetensi Pegawai PUPR Kota Sorong melalui Praktik Pengelolaan Jaringan Komputer (Lembaga Pengembangan Kinerja Dosen, 2026)
The computer network management practice at the Sorong City Public Works and Public Housing (PUPR) Office aims to improve the technical competence of employees in understanding, operating, and maintaining computer network devices, both hardware and software. This activity was carried out through four stages: observation, socialization, training, and evaluation, with a hands-on approach that emphasized direct participant involvement as the key to competency improvement. The results of the activity showed that employees gained a better understanding of network device configuration, cable management, and the use of network support software, and were able to solve simple technical problems independently. Post-training evaluations showed a significant increase in participants' technical abilities, which had a positive impact on operational efficiency and service quality at the agency. Thus, the hands-on practice supported by intensive mentoring proved effective in developing human resource competencies in the field of computer networks and supporting digital transformation within the Sorong City PUPR environment.